Stress stabilization behaviors in skin under small tensile loads in-Vitro - Wan Abas, W.A.B. (1995)
The response of human skin to ''stress relaxation'' tests at low loads in vitro was investigated. A number of behaviours, other than those already well established and documented, were observed. The significant behaviours are pure recovery and relaxation-recovery. Other behaviours observed are temporary stress recovery during the relaxation process, and momentary sudden non-linear drop in stress value followed by a second relaxation. The pure recovery and relaxation-recovery responses are repeatable. The latter represents the transitional response between the well-known behaviour of stress relaxation and the behaviour of stress recovery.